2021
DOI: 10.3389/fneur.2020.607221
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pathophysiology Predicts That Ischemic Stroke Occurrence Is an Expectation, Not an Exception—A Systematic Review

Abstract: Clinical reports of neurological manifestations associated with severe coronavirus disease 2019 (COVID-19), such as acute ischemic stroke (AIS), encephalopathy, seizures, headaches, acute necrotizing encephalitis, cerebral microbleeds, posterior reversible leukoencephalopathy syndrome, hemophagocytic lymphohistiocytosis, peripheral neuropathy, cranial nerve palsies, transverse myelitis, and demyelinating disorders, are increasing rapidly. However, there are comparatively few studies investigating the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 160 publications
(232 reference statements)
1
62
0
7
Order By: Relevance
“…In addition to these studies, all the others found in this review analyzed heterogenic populations of patients with COVID-19, from mild to severe. In this context, a recent editorial and a systematic review provided a detailed overview into the spectrum of mental disorders that can occur during the intermediate and long-term phases of COVID-19 in mild-to-critical patients (114,115). The most frequent neurological long-term symptoms in these patients were myalgia, arthralgia, sleeping troubles, and headache (46,50,61,116).…”
Section: Persistent Neurological Symptoms and Olfactory Dysfunctionsmentioning
confidence: 99%
“…In addition to these studies, all the others found in this review analyzed heterogenic populations of patients with COVID-19, from mild to severe. In this context, a recent editorial and a systematic review provided a detailed overview into the spectrum of mental disorders that can occur during the intermediate and long-term phases of COVID-19 in mild-to-critical patients (114,115). The most frequent neurological long-term symptoms in these patients were myalgia, arthralgia, sleeping troubles, and headache (46,50,61,116).…”
Section: Persistent Neurological Symptoms and Olfactory Dysfunctionsmentioning
confidence: 99%
“…The increased risk of these events is believed to be due to a hyperinflammatory/hypercoagulable state, and altered endothelial cell function resulting from the SARS-CoV-2 infection (Figure 2) [77][78][79][80][81]. Several studies have reported a significant increase in neutrophil-to-lymphocyte ratio (NLR), C-reactive protein (CRP), and serum ferritin in COVID-19 patients with ischemic stroke, which could predict mortality in these patients [82][83][84][85][86][87]. Neutrophilia (increase in neutrophils) described in these patients results in the overproduction of neutrophil extracellular traps (NETs), which has been shown to increase thrombi formation [88][89][90].…”
Section: Cerebrovascular Diseasesmentioning
confidence: 99%
“…Similar transcription factors are activated and remain so during the first months as oedema subsides, thus inducing chronic inflammation and suppressing immunological recovery. 23,24 ) 4. Prolonged alterations in the balance between the renin-angiotensin-aldosterone system and the downregulated ACE2 pathways are likely to promote end-organ dysfunction in the setting of acute COVID-19.…”
Section: Box 1 Pathobiology Of Covid-19 and Brain Involvement Illustrates The Shared Mechanisms Of Pathobiology Of Acute Ischaemic Strokementioning
confidence: 99%